A second-generation expression system for tyrosine-sulfated proteins and its application in crop protection. Issue 4 (27th November 2015) - Schwessinger, Benjamin; Li, Xiang; Ellinghaus, Thomas L.; Chan, Leanne Jade G.; Wei, Tong; Joe, Anna; Thomas, Nicholas; Pruitt, Rory; Adams, Paul D.; Chern, Maw Sheng; Petzold, Christopher J.; Liu, Chang C.; et al.
Abstract : The synthetic biological production of posttranslationally modified proteins enables control of biological processes in plants and animals. Abstract : Posttranslational modification (PTM) of proteins and peptides is important for diverse biological processes in plants and animals. The paucity of heterologous expression systems for PTMs and the technical challenges associated with chemical synthesis of these modified proteins has limited detailed molecular characterization and therapeutic applications. Here we describe an optimized system for expression of tyrosine-sulfated proteins in Escherichia coli and its application in a bio-based crop protection strategy in rice.